2012
DOI: 10.1590/s1677-04202012000400006
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response of oil palm interspecific hybrids (Elaeis oleifera H.B.K. Cortes versus Elaeis guineensis Jacq.) to water deficit

Abstract: 'U1937'='U1914'>'U1273'), and under water deficit ('U1937'>'U1914'>'U1859'>'U1273').]]>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 16 publications
0
13
0
5
Order By: Relevance
“…Only in recent years, a wide range of characteristics of O×G interspecific hybrids has been thoroughly studied and described: yield and morphology [15][16][17][18][19]; phenological stages [20]; genome size [21,22]; sensitivity to water stress [23,24]; physiological and biochemical response to aluminum toxicity [25]; nutritional status [26]; seed germination [27]; fruit abscission process [28]; and mycorrhization process [29]. Even a comparative characterization of the physiological and biochemical performance of seedlings of O×G hybrids grown in hydroponics was carried out [30].…”
Section: Introductionmentioning
confidence: 99%
“…Only in recent years, a wide range of characteristics of O×G interspecific hybrids has been thoroughly studied and described: yield and morphology [15][16][17][18][19]; phenological stages [20]; genome size [21,22]; sensitivity to water stress [23,24]; physiological and biochemical response to aluminum toxicity [25]; nutritional status [26]; seed germination [27]; fruit abscission process [28]; and mycorrhization process [29]. Even a comparative characterization of the physiological and biochemical performance of seedlings of O×G hybrids grown in hydroponics was carried out [30].…”
Section: Introductionmentioning
confidence: 99%
“…That is, for both hybrids the maximum A (8:00 h) in the irrigated plants varied between 7 and 8 μmoL m -1 s -1 , and for plants under water deficit 0.36 and 0.84 μmoL m -2 s -1 . Both Suresh et al (2012) and Méndez et al (2012) found no negative A values under stress conditions, which only occurred for BRS C 2501 and BRS Manicoré in the late afternoon.…”
Section: Discussionmentioning
confidence: 84%
“…In seedlings of oil palm hybrids, Suresh et al (2012) demonstrated that A drops from 6.20 μmoL m -2 s -1 in irrigated plants to 0.05 μmoL m -2 s -1 in plants subjected to water deficit, which Ψ w was around -3.5 to 4.0 MPa. Méndez et al (2012) observed that in oil palm hybrids, the decrease in Ψ w from -0.5 MPa to -2.0 MPa caused the reduction in A of mean values of 6.3 μmoL m -2 s -1 in irrigated plants and 0.8 μmoL m -2 s -1 in plants subjected to stress. In this experiment, the effects of water deficit on A of BRS C 2501 and BRS Manicoré were very similar to the results obtained by Suresh et al (2012) and Méndez et al (2012).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations